Basic oxygen furnace (BOF) slag as an additive in sodium carbonate-activated slag cements - Stefanini, Laura; Walkley, Brant; Provis, John L. (Materials and structures, 2024)
Basic oxygen furnace slag (BOFS) is a high-volume waste resulting from the production of steel from pig iron. Due to its high free lime content, BOFS is difficult to recycle and/or include into conventional cement systems. Alkali-activation technology offers a pathway to transform industrial wastes such as BOFS into low-carbon cements. Alternative precursors for cement systems are needed as the reliance on commonly used materials like ground granulated blast furnace slag (GGBFS) is becoming unsustainable due to decreasing availability. This study investigates alkali-activated cements incorporating 20 and 30 wt.% of naturally weathered BOFS as a replacement for GGBFS, in both sodium silicate- and sodium carbonate-activated systems. A fraction of BOFS subject to mechanical activation is compared against the untreated BOFS in the 20 wt.% systems. It is observed that in naturally weathered BOFS, a significant portion of the free-lime is found to convert to portlandite, which accelerates alkali-activation kinetics. In sodium silicate-activated systems, the high pH of the activator results in incomplete reaction of the portlandite present in BOFS. The sodium carbonate-activated system shows near complete conversion of portlandite, causing an acceleration in the kinetics of reaction, setting, and hardening. These findings confirm the viability of sodium carbonate activated GGBFS-based systems with only a minor loss in strength properties. BOFS can be utilised as a valuable cement additive for the production of sustainable alkali-activated cements utilising sodium carbonate as a less carbon-intensive activator solution than the more commonly used sodium silicate. Mechanical activation of BOFS offers further optimisation potential for alkali-activation.